Assessment of Noninvasive Markers of Liver Fibrosis in Patients With Chronic Hepatitis C in Ethiopia. Issue 4 (3rd November 2020) - Desalegn, Hailemichael; Chanie, Yemisrach; Shume, Paulos; Delil, Miftah; Gupta, Neil; Johannessen, Asgeir
Abstract : Watch a video presentation of this article